Children struggle towards discrimination in A Little Princess by Frances Hodgson Burnett - Ainul Hamdiyah; Rini Susanti Wulandari (Universitas Negeri Semarang, 2025)
This study examines children's struggles in facing discrimination as depicted in A Little Princess by Frances Hodgson Burnett using the psychological Self-Determination Theory (SDT) approach by Ryan and Deci, which focuses on the fulfilment of basic psychological needs: autonomy, competence, and relatedness. In addition, Erikson's psychosocial development theory, particularly the stage of ‘industry versus inferiority,’ relates to the development of school-age children. Through this approach, the study should be able to deeply reveal the psychological and social processes through which Sara resists injustice within a social context. This study uses the qualitative descriptive method with a literary content analysis approach to explore Sara Crewe's struggle against discrimination. The results show that the novel uncovers the complex mechanisms behind Sara's independence, offering valuable lessons for educators, parents, and mental health practitioners in fostering children's resilience amid adversity.